Torrefaction of oil palm fronds for co-firing in coal power plants - Hun, Shen Lau; Hoon, Kait Ng; Suyin, Gan; Seyed, Amirmostafa Jourabchi (Elsevier, 2018)
Torrefaction of biomass is a thermochemical process to enhance its fuel characteristics such as energy density and hydrophobicity. In this study, oil palm frond, a highly abundant agricultural waste in Malaysia is the feedstock of interest to investigate the influence of torrefaction temperature on its thermochemical properties. A single holding time of 30 min is used, with temperatures in the range of 200°C to 300°C (25°C increments). The mass and energy yields, as well as energy densification ratio are investigated, along with proximate analysis. Both mass and energy yield decreased with increasing torrefaction temperatures. The higher heating value (HHV) of torrefied oil palm fronds increased with increasing torrefaction temperature. Mild torrefaction temperatures (200°C - 225°C) showed insignificant improvements to HHV and slight reductions in mass and energy yields. Moderate and high torrefaction temperatures increased HHV significantly, while mass and energy yields continued to decrease. The optimum torrefaction temperature is determined to be at 250°C, giving the torrefied oil palm frond a respectable HHV of 26.62 MJ/kg, while maintaining an energy yield of 92.70%. This is within the range of HHV of coal, thus positioning torrefied oil palm frond as a suitable co-firing fuel for coal power plants